Examining Greenwashing’s Impact on Performance with ESG as a Buffer - Dian Widiyati; Neneng Hasanah (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
In the Fast-Moving Consumer Goods (FMCG) sector, greenwashing has become a widely discussed phenomenon. This industry is closely connected to consumers because its products are used daily, ranging from food and beverages to personal care items. Furthermore, corporate financial performance has become a central concern for both shareholders and stakeholders. Corporate performance often focuses primarily on commercial objectives while neglecting ecological and social aspects. This study aims to analyze the effect of greenwashing on corporate performance, evaluate the influence of Environmental, Social, and Governance (ESG) factors on corporate performance, and examine the role of ESG as a moderating variable in the relationship between greenwashing and corporate performance. The study population consists of Fast-Moving Consumer Goods (FMCG) companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The population in this study consisted of 57 companies, and the sample included 14 companies over a five-year period, resulting in a total of 70 observations. The sampling technique used was purposive sampling, and the data were analyzed using Moderated Regression Analysis (MRA) with EViews. The results show that greenwashing has a negative effect on corporate performance, ESG has a positive effect on corporate performance, and ESG significantly moderates the relationship between greenwashing and corporate performance. This research provides theoretical contributions to the sustainability literature as well as practical implications for companies, investors, and regulators in enhancing information transparency and ESG implementation.